KAJIAN POTENSI PENERAPAN EXTENSIVE GREEN ROOF BERBASIS STRUKTUR KAYU DI INDONESIA - Ika Rahmawati Suyanto; Widyastuti Kusuma Wardhani (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2023)
The availability of green space is decreasing along with the increase in population. Since then the land has been replaced by buildings as more people need a place to support human activities. As a result, the absorption of heat increases, causing the temperature in urbanized areas are higher relative to outlying areas (Urban Heat Island). Therefore, some efforts need to be made to reduce heat absorption, one of which is by applying the green roof. A strong roof structure and roof panel are required to implement green roofs. Wood is a material that has both strength and lightweight. However, the use of wood panels for roofing is not common in tropical areas due to the high rainfall. The wood roofing still has a potential to be used through the application of green roof technology that accommodate a waterproof layer and is not easily degraded by planting media. This study aims to examine the potential use of green roofs which made of wood structures and wood roofing in a tropical climate.